1964
DOI: 10.1128/jb.88.6.1580-1584.1964
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGICAL STATE OF ESCHERICHIA COLI AND THE INHIBITION OF DEOXYRIBONUCLEIC ACID SYNTHESIS BY PHENETHYL ALCOHOL

Abstract: Treick , R. W. (Indiana University, Bloomington), and W. A. Konetzka . Physiological state of Escherichia coli and the inhibition of deoxyribonucleic acid synthesis by phenethyl alcohol. J. Bacteriol. 88: 1580–1584. 1964.—The effects of concentration of phenethyl alcohol (PEA) and the physiological state of the cells on inhibition of macromolecular synthesis in Escherichia coli were investigated. Deoxyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Findings demonstrating non-specificity of the inhihitor have been reported for other organisms as well (Slepecky 1963. Xonoyama and Ikeda 1964, White and White 1964, Treick and Konetzka 1964, Kosenkranz et al 1964).…”
Section: Introductionmentioning
confidence: 72%
“…Findings demonstrating non-specificity of the inhihitor have been reported for other organisms as well (Slepecky 1963. Xonoyama and Ikeda 1964, White and White 1964, Treick and Konetzka 1964, Kosenkranz et al 1964).…”
Section: Introductionmentioning
confidence: 72%
“…It was reported that the bacteriostatic action of phenethyl alcohol was characterized by the specific and reversible inhibition of DNA synthesis [3]. It was reported that the DNA being replicated at the time of phenethyl alcohol addition completes its replication cycle and, although there is gal net synthesis of RNA and protein, no initiation of a second cycle of DNA replication occurs until the removal of the inhibitor [19].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohpl on Bacterial Generation-The effect of phenethyl alcohol on the generation of E. coli NlHJ JC-2 was measured to ascertain the concentration which wdbld effectively retard bacterial generation by the inhibition of DNA synthesis (9). The results ( Fig.…”
Section: Effect Of C E L L Cycle At the Time Of Drug Addition-effect mentioning
confidence: 99%